TINJAUAN YURIDIS TANGGUNG JAWAB LINGKUNGAN DAN SOSIAL PT MANDIRI PRIMA PASCA PENAMBANGAN BATU BARA - Ihsan Sanjaya (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Mining is carried out solely for the development of the State and the welfare of the people as stated in article 33 paragraph (3) of the 1945 Constitution but in reality it is not like that mining companies only reap their own personal benefits without thinking about the surrounding environment that is still far from welfare If the Company does not implement that responsibility, then the company will get administrative sanctions up to the revocation of mining permits, this is the reason for the author to raise the title of juridical review if the company does not carry out environmental and social responsibility, the research method used is normative juridical, the form of contribution that is what a company does is with programs in several fields such as community empowerment, infrastructure improvement and development and environmental preservation. The Government in terms of Social and Environmental Responsibility (TJSL) or Community Development and Empowerment (PPM) has carried out law enforcement efforts as evidenced by the existence of relevant laws and regulations. Keywords: Responsibility, Mining and Company.